Analisis Peraturan Pencegahan Kekerasan Seksual di Perguruan Tinggi dalam Tinjauan Al-Qur’an dan Hadis - Musonnif Alfi; Zahara Baqiyatus Sholekhah; Sunanul Baroroh (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) IPMAFA, 2022)
Regulation of the Minister of Education, Culture, Research, and Technology Number 30 of 2021 concerning the prevention of sexual violence in Higher Education arises because there are many cases of sexual harassment that occur in the Higher Education environment and there is no specific law to handle it. On the other hand, the majority of the population of Indonesia is Muslim, with the main teachings being the Koran and Hadith which also prohibit adultery and sexual violence. On this basis, this study aims to analyze Permendikbudristek Number 30 of 2021 in terms of the perspective of Islam. The method used in this study is a qualitative method with analytical techniques using content analysis. The primary source of research data refers to Permendikbudristek Number 30 of 2021 while secondary data is obtained through scientific journals, books, national news, and phenomena circulating in the community. The results of this study indicate that Permendikbudristek Number 30 of 2021 is not in accordance with Islamic teachings so that a review is needed so that Permendikbudristek is in line with and does not conflict with Islamic teachings contained in the Koran and Hadith.